KORELASI ANTARA MOTIVASI DAN GAYA BELAJAR DENGAN NILAI KOGNITIF PADA PEMBELAJARAN TEMATIK KELAS IV - Trioktaviani Aling; Tahmid Sabri; Dyoty Auliya Vilda Ghasya (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2021)
AbstractThis study aims to determine the correlation between learning motivation andlearning style with students' cognitive values in the fourth grade thematiclearning at State Elementary School 03 South Pontianak. The research methodused is descriptive method in the form of relationship studies by using correlationstudies. The population in this study amounted to 129 students and the sampleused was class IV D totaling 32 students. Data collection techniques in this studyare direct communication techniques, indirect communication techniques anddocumentary study techniques. The instruments (data collection tools) of thisstudy were interviews (interviews), questionnaires (questionnaires) and cognitivevalue documents. The results showed that students' learning motivation at theState Elementary School 03 South Pontianak was 83.94% in the "Good" categoryand 71.83% in the student learning style in the "Enough" category. While thecognitive value of the students of South Pontianak State Elementary School 03obtained an average of 88.09 in the "Good" category. Based on the results ofstatistical calculations using the multiple correlation formula to calculate thecorrelation between learning motivation and learning style with students'cognitive values, it is obtained r count of 0.213, while r table for N = 32 and asignificance level of 5% of 0.349 means r count < r table or 0.213 < 0.349. Basedon the results of the study, the correlation between learning motivation andlearning style with students' cognitive scores in class IV thematic learning atState Elementary School 03 South Pontianak is in the low category.Keywords: Cognitive Value, Correlation, Learning Motivation, Learning Style